Data and code related to "Direct measurements of mRNA translation kinetics in living cells", by Metelev et al. - Metelev, Mikhail; Lundin, Erik; Volkov, Ivan L.; Gynnå, Arvid Heden; Elf, Johan; Johansson, Magnus (Uppsala University, 2022)
This repository contains microscopy data and analysis code related to the publication: Metelev et al., "Direct measurements of mRNA translation kinetics in living cells".

The study includes single-particle tracking of ribosomal subunits in live E. coli cells, for analysis of translation kinetics under different conditions.

A detailed list of files and file organization can be found in the readme text file.
Keywords: Biochemistry and cell biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi